2022
DOI: 10.1186/s12889-022-12733-9
|View full text |Cite
|
Sign up to set email alerts
|

Work fatigue among Lebanese physicians and students during the COVID-19 pandemic: validation of the 3D-Work Fatigue Inventory (3D-WFI) and correlates

Abstract: Background Work fatigue is a work-related condition that affects physicians’ health, work attitude safety and performance. Work fatigue affects not only medical workers but can also leave a negative impact on patients. With the burden of the COVID-19 pandemic as well as the economic crisis Lebanese doctors have been facing in the last 2 years, the aim of our study was to validate the 3D-Work Fatigue Inventory (3D-WFI) among Lebanese physicians and assess the rate and correlates of work fatigue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 61 publications
4
18
0
9
Order By: Relevance
“…Moreover, a study by Sfeir et al, which assessed work fatigue using the 3D-WFI (3D-Work Fatigue Inventory) questionnaire, demonstrated that out of 401 medical students and doctors under study, 66.1%, 64.8%, and 65.1% respondents showed medium or high levels of emotional, mental, and physical work fatigue, respectively [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a study by Sfeir et al, which assessed work fatigue using the 3D-WFI (3D-Work Fatigue Inventory) questionnaire, demonstrated that out of 401 medical students and doctors under study, 66.1%, 64.8%, and 65.1% respondents showed medium or high levels of emotional, mental, and physical work fatigue, respectively [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, an increasing number of authors, when searching for predictors of lockdown-related fatigue, indicate a variety of variables, including socio-demographic variables [ 6 , 15 , 65 ] or an individual’s resources such as the skills of coping and personal immunity [ 15 , 60 ]. The above studies identified gender as an important predictor of fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…The 3D‐WFI composed of 18 Items was used to evaluate physical, mental, and emotional work fatigue (Frone & Tidwell, 2015). This scale is validated in Lebanon (Sfeir et al, 2022) and is divided into 3 sections related to the three separate energy resources or factors and each section include 6 questions with similar structure respectively. Greater levels of fatigue are reflected by higher scores of these three scale parts.…”
Section: Methodsmentioning
confidence: 99%
“…Relevance of the topic was formulated in times of COVID-19 pandemic, as it brought additional stress to people. For example, this perceived stress can negatively impact learning engagement and academic outcomes of university students (Lu et al, 2022;Sfeir et al, 2022). At the same time, mindfulness can become a regulator that helps reduce the level of perceived stress (Castillo-Sánchez et al, 2022;Xu et al, 2022).…”
Section: Justification Of the Choice Of Articles And Goals And Object...mentioning
confidence: 99%